Ultra-sensitive solid-phase Microextraction–Gas Chromatography–Mass spectrometry determination of polycyclic aromatic hydrocarbons in snow samples using a deep cavity BenzoQxCavitand. (September 2022) - Riboni, N.; Amorini, M.; Bianchi, F.; Pedrini, A.; Pinalli, R.; Dalcanale, E.; Careri, M.
Abstract: A very sensitive and selective solid-phase microextraction-gas chromatography-mass spectrometry method based on the use of a deep cavity BenzoQxCavitand as innovative coating was developed and validated for the simultaneous determination of the 16 US-EPA priority pollutants polycyclic aromatic hydrocarbons (PAHs) in snow samples at ultra-trace levels. The presence of a 8.3 Å deep hydrophobic cavity allowed the engulfment of all the 16 PAHs, providing enhanced selectivity also in presence of interfering aromatic pollutants at high concentration levels. Validation proved the reliability of the method for the determination of the investigated compounds achieving detection limits in the 0.03–0.30 ng/L range, good precision, with relative standard deviations <18% and recovery rates in the 90.8(±2.1)%-109.6(±1.0)%. The detection of low-molecular weight PAHs in snow samples from Antarctica and Alps confirms the widespread occurrence of these compounds, thus assessing the impact of anthropogenic activities onto the environment. Graphical abstract: Image 1 Highlights: A deep cavity BenzoQxCavitand as selective SPME coating. Ultra-sensitive detection of PAHs from Antarctic and Alpine snow samples. Completely automatized method requiring reduced sample handling and volumes. LODs in 0.03–0.30 ng/L range.